The current state of food industry development - Zorina, Anna; Vlasenko, Ludmila (My University, 2014)
At the present stage of development had the difficult economic situation of the entire national economy of Ukraine and especially is food industry, as this industry is very dependent on other industries: engineering, chemical, petroleum, and especially the solvency of the population. In this difficult time most citizens have to save every coin of their own earnings, as well as our food industry is forced to compete with neighboring countries - where food is cheaper. However, despite the difficult financial situation, many enterprises are reconstruction and technical re-equipment of production; introduce new type of high- quality products in a modem package.
Keywords: development; economic situation; food industry; економічне становище; харчова промисловість; розвиток; развитие; экономическое положение; пищевая промышленность; кафедра ділової іноземної мови та міжнародної комунікації